2021
DOI: 10.1016/j.cattod.2020.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-metal oxides coupling for CH4-CO2 transformation into syngas and/or hydrocarbons, oxygenates

Abstract: Dry reforming of methane was investigated by non-thermal plasma coupled with different metal oxides: BaO, La2O3, ZnO, CaO, -Al2O3, MgO, γ-Al2O3, TiO2 and CeO2. The deposited power was fixed at 8W and the total gas flow at 40 mL.min-1 (75% helium as diluent). Electrical characterization showed that the CO2 and CH4 conversions were enhanced (from 5.6 to 30.6% for CH4 and from 1.9 to 16.1 % for CO2) when the permittivity was reduced from 2903 to 4.1, respectively. Methanol selectivities were favored for the oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The calculations, reported elsewhere, showed that the type of plasma and its propagation inside the pores are defined by the permittivity of solids [40,41] . It has been also shown that the materials with a low permittivity value demonstrate a greater activity in plasma catalysis compared to the ones with a high value [12,42] . It is believed that with the increase of permittivity, the charge density stored in the material can be increased, however the volume of efficient discharge is reduced, and the global transformation of reactants is limited at a fixed value of deposited power.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The calculations, reported elsewhere, showed that the type of plasma and its propagation inside the pores are defined by the permittivity of solids [40,41] . It has been also shown that the materials with a low permittivity value demonstrate a greater activity in plasma catalysis compared to the ones with a high value [12,42] . It is believed that with the increase of permittivity, the charge density stored in the material can be increased, however the volume of efficient discharge is reduced, and the global transformation of reactants is limited at a fixed value of deposited power.…”
Section: Resultsmentioning
confidence: 96%
“…[40,41] It has been also shown that the materials with a low permittivity value demonstrate a greater activity in plasma catalysis compared to the ones with a high value. [12,42] It is believed that with the increase of permittivity, the charge density stored in the material can be increased, however the volume of efficient discharge is reduced, and the global transformation of reactants is limited at a fixed value of deposited power. Indeed, using ferroelectric pellets (BaTiO 3 , dielectric constant: 1 250-10 000) Gomez-Ramirez et al [43] observed that discharges were mainly located at the contact point between pellets and electrodes, and did not extend through the whole volume.…”
Section: Permittivitymentioning
confidence: 99%
“…DBD plasmas are highly nonequilibrium, i.e., the temperature of the electrons is much higher than that of the gas. , The low temperature of the gas allows incorporation of a catalyst into the DBD discharge region, which can improve the system efficiency. Various packing materials with both noncatalytic and catalytic properties have been used for plasma-catalytic DRM, including glass beads, metal oxides, supported catalysts with both transition and noble metals, , zeolites, and metal–organic frameworks . However, the negative issue of coke deposition due to the fast rate of CH 4 dissociation induced by plasma imposes restrictions on the stability of catalysts and hinders further understanding of the mutual interaction between plasmas and catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Alumina was chosen due to its low dielectric constant (9-30), favorable to plasma -catalysis coupling [25]. Indeed, we show in a previous paper that CH4 and CO2 conversions can be correlated with the dielectric constant of the material, the lower the dielectric constant, the higher the conversions for both CO2 and CH4 [26].…”
Section: Introductionmentioning
confidence: 99%